SISTEM PENDUKUNG KEPUTUSAN CERDAS PENGEMBANGAN AGROINDUSTRI KARET ALAM DENGAN PENDEKATAN PRODUKTIVITAS HIJAU MENGGUNAKAN FUZZY AHP - Hendra, Marimin, dan Yeni Herdiyeni TIP (Jurnal Teknologi Industri Pertanian, 2014)
ABSTRACT An industry that is closely related to environmental issues is the natural rubber industry. Production increase of natural rubber related with increase of garbage or waste that cause negative impact to the environment. Productivity is comparison between production outcome against resources used and productivity is one important indicator of production outcome assessment. The objectives of this research were to design software  of intelligent decision support systems to measure the green productivity, to provide solutions and simulations an increase of productivity in the natural rubber agroindustry. The software used  a fuzzy-rule to measure green productivity based on economic data and seven sources of waste generation data such as energy, water, materials, garbage, transportation, emissions, and biodiversity. Fuzzy analytical hierarchy process (Fuzzy AHP) was used to select the four alternatives on cultivation and processing of natural rubber agroindustry which have major influence on productivity improvement and reduce environmental impact which became a green productivity concept. The final results software was a simulation of the best alternative in the form of seven sources of waste generation and economic data.   Keywords:intelligent decision support system, fuzzy rule-base,fuzzy AHP, green productivity